Estimation of the economic impact of a bluetongue serotype 4 outbreak in Tunisia - Ben Salem, Ameni; Ben Aicha, Elhem; Kalthoum, Sana; Dhaouadi, Anissa; Hajlaoui, Haikel; Bel Haj Mohamed, Bassem; Ben Slimen, Imed; Khalfaoui, Wiem; Gharbi, Raja; Guesmi, Kaouther; Ben Ali, Mehdi; Fatnassi, Naouel; et al. (Frontiers in Veterinary Science, 2024)
Since 1999, Tunisia has experienced multiple occurrences of Bluetongue (BT) outbreaks, leading to numerous reported cases of infection and mortality in flocks. The re-emergence of the disease in 2020 caused substantial economic losses in cattle, attributed to the incursion of serotype BTV-4.To evaluate the economic impact of the recent BT episode, we conducted a retrospective study on outbreaks that occurred in Tunisia between August and November 2020, focusing on the impact at the owner's level and its effects on both small ruminants and cattle. A total of 234 ruminant farms (sheep, cattle, and mixed) were randomly selected across Tunisian governorates and included in the study to estimate both the direct and indirect costs of these outbreaks.Total costs were calculated as the sum of losses and expenditures resulting from the BT outbreaks. At the animal level, total losses were estimated to range between 116.280 and 207.086 TND for one infected ewe (€33.721 and 60.055). For one lactating cow, costs varied between 2,590.724 and 3,171.107 TND (€751.310 and 919.621). In cattle, exposure to BTV led to a daily unit milk yield decrease of 12.50 to 14.66 L over an average period of 5 months.Diseased sheep experienced weight loss ranging between 4 and 10 kg during the BT outbreaks.The total mean cost of the 2020 BT outbreak in Tunisian investigated farms was estimated at 1,935 million TND (million €561.15) (range: 1,489 and 2,474 million TND; 431.81 and million €717.46). The most influential costs of the total BT outbreaks were the decrease in milk yield, mortality, and veterinary treatment. This study gives valuable insights on the economic impact of the incursion of a new serotype of BT in a naive population in Tunisia. Considering the substantial costs incurred, it is imperative that this disease receives increased attention from stakeholders, including animal owners, veterinary services, practitioners, and decision-makers.